PENGEMBANGAN BUKU REFERENSI RANGKAIAN RLC UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI MAHASISWA SEBAGAI UNSUR KETERAMPILAN ABAD 21 - yaspin yolanda; Apit Fathurahman (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2023)
This research is motivated by the low level of student competency skills in collaborating when presenting the results they have learned, students are not yet skilled in interpreting the results of their findings so they are still hesitant in drawing conclusions. Furthermore, students' activities in collaborating, working together only when discussing material, have not shown solid cooperation in making simple electronics crafts. The aim is (1) to measure the validity, practicality and effectiveness of the product. (2) know collaboration skills. Research Location at PGRI Silampari University from January to July 2022. The subjects are third semester physics education students. The method used is research and development (research and development) ADDIE model. The instruments used are observation sheets, questionnaires and tests. Data analysis is in the form of quantitative descriptive. The research results show that this book is good to use. This book can facilitate students to work on electronic component questions contained in competency test questions. To see the feasibility of the book being developed, it is necessary to carry out a validation process. The overall validation results are valid with a validity level of 39.5% (valid). The average student response was 3.26 in the practical category and the effectiveness of learning using the collaborative method regarding the RLC series. There was an increase in learning outcomes and students' skills in using multimeter and oscilloscope measuring instruments of 85.13% in the category of increasing in the realm of knowledge and skills, then in the realm of The attitude shows that 50% of students are developing according to expectations, 25.6% are developing and 29.4% are starting to develop.